SUNAT PEREMPUAN DALAM PERSPEKTIF BUDAYA, AGAMA DAN KESEHATAN (STUDI KASUS DI MASYARAKAT DESA BADDUI KECAMATAN GALESONG KABUPATEN TAKALAR SULAWESI SELATAN) - Islamiyatur Rokhmah; Umu Hani Edi Nawangsih (Universitas Aisyiyah Yogyakarta, 2015)
This study aimed to obtain information about the process circumcision women, the influence of tradition and religion as well as the views of healthcare workers wearing sunat women in rural sub-district Baddui Galesong Takalar. This study uses a qualitative method, the retrieval of data using in-depth interviews and Focus Group Discussions (FGD). Analysis of the data by means of descriptive steps: data reduction, categorization and analysis-interpretation. The study showed villagers Bodia still believe that female circumcision should be done. This is influenced by factors of cultural and religious interpretations. If seen the female circumcision is still not sterile and harmful to women's reproductive health.Keywords: female circumcision, culture, religion and health perspective